2017
DOI: 10.4103/jcas.jcas_89_17
|View full text |Cite
|
Sign up to set email alerts
|

Safety and early satisfaction assessment of patients seeking nonsurgical rhinoplasty with filler

Abstract: Background:Nonsurgical aesthetic treatments are usually preferred by patients because their effects are visible immediately after the treatment and patients can return to their normal activities on the same day. Although many studies have indicated safety and efficacy of filler injection to improve facial appearance, it is not absolutely confirmed for nose reshaping.Objectives:To assess the safety and early satisfaction of 52 consecutive patients underwent nonsurgical rhinoplasty with an injection of a 20-mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…10 These statistics were verified within this study and also align with previously stated ~95% satisfaction rating in the literature. 8 Based on this study, the most common self-reported nasal defects include a bump, a hump, and a crooked shape. A bump is defined as a convex irregularity of any area of the nose, and a hump most likely represents a traditional dorsal hump.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…10 These statistics were verified within this study and also align with previously stated ~95% satisfaction rating in the literature. 8 Based on this study, the most common self-reported nasal defects include a bump, a hump, and a crooked shape. A bump is defined as a convex irregularity of any area of the nose, and a hump most likely represents a traditional dorsal hump.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies on nonsurgical rhinoplasty have only been single clinic studies that look at the satisfaction rate of a small number of patients. 8,9 Khansa et al performed a study in 2015 using RealSelf that examined thousands of surgical rhinoplasty reviews and demonstrated the importance of social media in understanding patients' satisfaction after cosmetic surgery. 3 In the age of social media, more and more patients use social media to share their experience and results with other prospective patients.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports, dating back to the middle of the 1980s, described the use of bovine collagen and silicone to address nasal reshaping. 9,10 In the following decades, the use of several types of HA and calcium hydroxyapatite 11–13 was described. The main concern with calcium hydroxyapatite is the lack of an antidote if any complication occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Only those studies utilizing hyaluronic acid fillers for non‐surgical rhinoplasty on humans or cadavers have been included in this review. Summary of study characteristics that were included has been illustrated in Table 1, 12,17‐27 which includes authors; country where the study has been conducted; no. of patients; age and gender of the patients; fillers used; parameters assessed; and results and adverse effects.…”
Section: Methodsmentioning
confidence: 99%